Fetal Distress Management due to Fever in Pregnancy: a Case Report - Ulhayah, Syiva; Zulfadli, Zulfadli (Medula, 2024)
As one of many body response to fight infection, trauma, etc., fever is a process that requires the work of cytokine, pyrogen, hypothalamus and many others. Therefore, a fever during pregnancy could potentially lead to complications such as infection and declining health problems, even fetal distress caused by the mom's infection or inflammatory condition. In the following case, a women had came with chief complaints of reappearing fever even after taking antipyretic medications as well as painful urination. The patient then diagnosed with partus premature imminens while getting into 34th week of pregnancy, as well as urinary tract infection and suspect of bacterial vaginosis. Observation of general conditions, vital signs and fetal heart rate were done, as well as some other medications were given to the patient. Vaginal swab was also scheduled for the patient. The immunology and serology lab test result were out in the next 24 hours and showed that positive dengue fever IgG and typhoid fever were indicated within IgM anti salmonella 6 scale result. Additional medications were added, yet signs of declining vital conditions of the patient as well as the fetus kept shown. Therefore, sectio caesarea delivery was needed. vital signs observation and medications were given post-operation. The raising awareness of pregnant women regarding fever during pregnancy had to be done to reduce any possible complications that could occur in the future. Pregnant women also need to increase their nutritional intake which can help increase the body's immunity so that pregnant women are not easily infected by bacteria, viruses and others.